Impact of Parameter on Nanostructured Lipid Carrier Formulation and Approach of the Carrier for Cancer Treatment: a Brief Study - L. Sahoo; G. K. Jena; C. S. Patro (Разработка и регистрация лекарственных средств)
Introduction. For the last decade, nanotechnology has been studied extensively in the pharmaceutical field. Among all the nanotechnology formulation areas, nanostructured lipid carrier is enormously researched by formulation scientists as it is one of the focused areas of lipid carrier for the effective formulation.Materials and methods. The nanostructured lipid carrier (NLC) consists of solid lipid, liquid lipid & surfactant for fabrication of formulation. Methods such as high energy methods, low energy methods and organic solvent-based methods are used for the preparation of NLC. As per literature study the High pressure homogenization is the most efficient method for fabrication of formulation.Results and discussion. This carrier system has significant advantages such as high drug entrapment, improved bioavailability, stability during storage, and targeting the site with a better-controlled release making it a prominent area for the formulator to emphasize on it. Although many drugs are formulated with a nanostructured lipid carrier, it is a concern for researchers to find out the effectiveness of formulation by studying the process parameter and safety.Conclusion. The present review was focused to study the impact of various parameters such as Lipid, surfactant, homogenization rate, preservative, Crystallinity, and surface charge on the formulation. The study also extended towards toxicity and biocompatibility, topical targeting & cancer treatment of the Nanostructured lipid carrier.